A Study of Potential Drug-Drug Interactions in Peptic Ulcer Patients in Dr. M. Djamil Hospital Padang in 2019 - Lola Azyenela; Ringga Novelni; Viora Lusiana Satri (Sanata Dharma University, 2023)
A peptic ulcer is a gastrointestinal tract disorder caused by excessive secretion of acid and pepsin by the gastric mucosa. The combined use of drugs in peptic ulcer management may potentially cause drug-to-drug interactions. Drug interactions are caused when two or more drugs interact and may affect the effectiveness of the other drugs. This study aims to analyze the potential drug reactions in peptic ulcer patients in the internal medicine ward of Dr. M. Djamil General Hospital Padang in 2019. This study was a descriptive, non-experimental study with retrospective data, while data analysis used Drugs.com and Medscape applications. The study results revealed that 29 patients fit the inclusion criteria and 5 (16.6%) potential drug pharmacokinetic interactions. The severity of drug interactions shows 4 cases (80%) with moderate severity potential and 1 case (20%) with minor severity potential. The study concluded that there were potential drug interactions in peptic ulcer patients in the internal medicine ward of Dr. M. Djamil General Hospital Padang in 2019.